Paired Reading and Paired Summarizing Strategy: Exploring Motivation and Effects Of EFL Students’ Reading Comprehension - Neni Triana (Fakultas Sastra - Universitas Muslim Indonesia, 2021)
Paired Reading and Paired summarizing is one teaching strategy that can use in teaching reading. The main purpose of this study is to find out the effects of Paired Reading and Paired Summarizing Strategy on students’ reading comprehension and motivation at SMK Abdurrab Pekanbaru. The design of this research is a quasi-experiment design with pre-test and post-test procedures. The total population is 97 students of the tenth grade. This research uses a cluster sampling technique to get samples. The total sample is 64 students. The sample is divided into two classes; the experimental class and the control class. The data are analyzed using the t-test method to find out whether there is a significant difference between the experimental class taught by using Paired Reading and Paired Summarizing as a treatment, and the control class is taught conventionally. it found that significant probabilities are higher than 0.05meaning that there is a significant difference in students' reading comprehension and learning motivation in the pre-test of both classes and post-test of both classes, and there is a significant difference in students' reading comprehension and learning motivation pre-test and post-test of experimental class. There is an effect of using Paired Reading and Paired Summarizing on students’ reading comprehension and learning motivation. At last, it suggested that the English teachers Paired Reading and Paired Summarizing in teaching are reading.